Synthetic and Nanotechnological Approaches for a Diagnostic Use of Manganese - Maddalena Sguizzato; Petra Martini; Lorenza Marvelli; Walter Pula; Markus Drechsler; Martina Capozza; Enzo Terreno; Lucia Del Bianco; Federico Spizzo; Rita Cortesi; Alessandra Boschi (Molecules, 2022)
The development of multimodal imaging techniques such as positron emission tomography (PET) and magnetic resonance imaging (MRI) allows the contemporary obtaining of metabolic and morphological information. To fully exploit the complementarity of the two imaging modalities, the design of probes displaying radioactive and magnetic properties at the same time could be very beneficial. In this regard, transition metals offer appealing options, with manganese representing an ideal candidate. As nanosized imaging probes have demonstrated great value for designing advanced diagnostic/theranostic procedures, this work focuses on the potential of liposomal formulations loaded with a new synthesized paramagnetic Mn(II) chelates. Negatively charged liposomes were produced by thin-layer hydration method and extrusion. The obtained formulations were characterized in terms of size, surface charge, efficiency of encapsulation, stability over time, relaxivity, effective magnetic moment, and in vitro antiproliferative effect on human cells by means of the MTT assay. The negatively charged paramagnetic liposomes were monodisperse, with an average hydrodynamic diameter not exceeding 200 nm, and they displayed good stability and no cytotoxicity. As determined by optical emission spectroscopy, manganese complexes are loaded almost completely on liposomes maintaining their paramagnetic properties.